Determinants of occupational burnout among primary school teachers in northern Malaysia - Omar, Siti Nur Zahirah; Muhamad Nazri, Hani Yasmien; Abu Samah, Ayuni Sahara; Muhamad Safri, Nur Ain; Zainol Rahman , Nurul Qistina; Mohamad Roslan, Mohamad Rafee (Journal of Islamic, Social, Economics and Development, 2026)
Occupational burnout among teachers has become a growing concern as it affects teachers’ well-being, job performance, and teaching effectiveness. In Malaysia, primary school teachers face various workplace challenges, including high workload, insufficient support, emotional demands, and difficulties in balancing work and family responsibilities. Although teacher burnout has been widely studied, further research is needed to understand its contributing factors, particularly among primary school teachers in Northern Malaysia. This study examines the relationship between workload, lack of support, emotional, self-efficacy, and work-family conflict with occupational burnout among primary school teachers. Using a quantitative correlational research design, data will be collected through structured questionnaires distributed to teachers in Kedah, Perak, Pulau Pinang, and Perlis. The findings are expected to provide insights into the key determinants of teacher burnout and support schools and educational authorities in developing effective strategies to enhance teachers’ well-being and create a supportive work environment.